Analyzing Grammatical Problems Faced by The Seventh Semester Students of Economic and Bussiness Faculty in Writing Abstract of Research: English - Siti Masluha (Journal of English Development, 2024)
This paper analyzes grammatical problems that the Economic and Business Faculty's seventh-semester students run across. By using a descriptive qualitative methodology, the study concentrates on abstract texts taken from eight articles that are part of the JUMAD journal, a well-known publication among the faculty members of economics and business. By careful analysis, typical grammatical problems seen in these abstracts are found and examined. The results illuminated a number of linguistic flaws, including misspellings, inconsistent verb tenses, repetition, ambiguity, and poor word choice. For students, these grammatical problems are major obstacles to both academic writing proficiency and effective communication. Although verb tense irregularities throw off the flow of ideas, spelling mistakes diminish the professionalism and credibility of the texts. Readers find the material hard to understand because of repetitions and unclear meanings. Furthermore, poor word selections can cause confusion and information misinterpretation. In general, knowing the linguistic difficulties students encounter in academic writing situations depends on the recognition and examination of these grammatical issues.